What your employees need and can't tell you : adapting to change with the science of behavioral economics - Palmer, Melina (Ascent Audio, 2022)
Adapting to change is part of life. In our highly competitive world, organizational change in the workplace is more and more essential for business success. Unfortunately for many of us, change is hard and managing change is even harder. Because we really don't know how the brain works, we and our employees don't know what makes us more receptive to change. Employees can't tell their managers what they need to "get on the train", and managers don't know either. In her first book, What Your Customer Wants and Can't Tell You, author and behavioral economics specialist Melina Palmer, applies the science of behavioral economics to unlocking what is behind customer decisions. Behavioral economics combines elements of economics and psychology to understand how and why people behave the way they do in the real world. Now, in her sequel, What Your Employees Need and Can't Tell You, she offers a highly actionable roadmap for business executives and managers faced with the task of instituting successful organizational change. What Your Employees Need and Can't Tell You delivers insights and research from behavioral economics and the greater behavioral sciences, presented in an enjoyable way that you can actually use to get results.